Nanoparticle assisted activity optimization and characterization of a bacterial phytase immobilized on single layer graphene oxide. (January 2017) - Dutta, N.; Raj, D.; Biswas, N.; Mallick, M.; Omesh, S.
Abstract: A thermostable phytase is a need of the hour towards prevention of environmental pollution by accumulation of phosphate. In this study, an extracellular phytase was purified from a strain of Bacillus subtilis obtained from cattle sheds in 24 Parganas (Kolkata, West Bengal). The native enzyme showed optimum activity at 42 °C and pH 8.5. In presence of magnesium nanoparticle (MgN), the graphene oxide (GO) immobilized enzyme showed 2.40 fold increased activity at 42 °C and more than 20 fold activity increment at 85 °C. The GO-MgN-phy complex (phytase coupled to MgN immobilized on graphene oxide) showed a decrease in Km by 3.29 folds at 42 °C and 6 folds at 85 °C. Again, the enzyme system showed 3 fold and 5.5 fold increase in Vmax at 42 °C and 85 °C respectively than the untreated enzyme. Compared to the untreated enzyme, energy of activation (Ea ) was lowered by 2.5 and 6 folds repectively at 42 °C and 85 °C for GO-MgN-phy. At 85 °C, the half life (t½ ) for GO-MgN-phy was 29.5 times than that of untreated enzyme with energy of dissociation (Ed ) being 1.45 fold higher than the untreated enzyme. Enzymatic activity of GO-MgN-phy was retained by 86.6%when tested for storage stability at 4 °C after 140 days. This nanoparticle assisted immobilization technique employed in developing a thermostable phytase enzyme could withstand high temperatures during the pelleting of animal feeds. The increased activity of the enzyme would be beneficial to breakdown phytic acid during storage of feeds. Graphical abstract: Highlights: MgN-phy showed enhanced activity and stability at 85 °C. GO-MgN-phy showed increased half-life at 85 °C. Lowered Km and increased Vmax for GO-MgN-phy 85 °C. Enzymatic activity of GO-MgN-phy retained after 180 min incubation. Stability of GO-MgN-phy enzyme system at 4 °C for more than 140 days.